2019
DOI: 10.1104/pp.18.01244
|View full text |Cite
|
Sign up to set email alerts
|

B-Box Containing Proteins BBX30 and BBX31, Acting Downstream of HY5, Negatively Regulate Photomorphogenesis in Arabidopsis

Abstract: Light-mediated seedling development is coordinately controlled by a variety of key regulators. Here, we identified two B-box (BBX)-containing proteins, BBX30 and BBX31, as repressors of photomorphogenesis. ELONGATED HYPOCOTYL5, a central regulator of light signaling, directly binds to the G-box cis-element present in the promoters of BBX30 and BBX31 and negatively controls their transcription levels in the light. Seedlings with mutations in BBX30 or BBX31 are hypersensitive to light, whereas the overexpression… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
107
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 79 publications
(112 citation statements)
references
References 47 publications
(96 reference statements)
5
107
0
Order By: Relevance
“…Additionally, photoreceptor phytochromes (PHYA and PHYB), and cryptochrome CRY2 are also known to undergo proteasomal-mediated degradation through direct interaction with COP1 (Jang et al 2010;Weidler et al 2012;Podolec and Ulm 2018). The positive photomorphogenesis-related factors HY5, HYH, LAF1, HFR1, PHYTOCHROME INTERACTING FACTOR 3 LIKE 1 (PIL1), PHYTOCHROME RAPIDLY REGULATED 1 (PAR1), PHYTOCHROME RAPIDLY REGULATED 2 (PAR2), B-BOX 4 (BBX4), B-BOX 21 (BBX21), and LIGHT REGU-LATED ZINC FINGER PROTEIN 1 (LZF1) and the negative regulators of photomorphogenesis phytochrome interacting factors PIF1, PIF3, B-BOX 25 (BBX25), B-BOX 28 (BBX28) directly interact with COP1, and their levels are regulated by the E3 ubiquitin ligase activity of COP1 (Holm et al 2002;Kim et al 2002;Datta et al 2006;Datta et al 2008aDatta et al , 2008bGangappa and Botto 2016;Xu et al 2016;Zhang et al 2017;Lin et al 2018;Heng et al 2019).…”
Section: Light Signalingmentioning
confidence: 99%
“…Additionally, photoreceptor phytochromes (PHYA and PHYB), and cryptochrome CRY2 are also known to undergo proteasomal-mediated degradation through direct interaction with COP1 (Jang et al 2010;Weidler et al 2012;Podolec and Ulm 2018). The positive photomorphogenesis-related factors HY5, HYH, LAF1, HFR1, PHYTOCHROME INTERACTING FACTOR 3 LIKE 1 (PIL1), PHYTOCHROME RAPIDLY REGULATED 1 (PAR1), PHYTOCHROME RAPIDLY REGULATED 2 (PAR2), B-BOX 4 (BBX4), B-BOX 21 (BBX21), and LIGHT REGU-LATED ZINC FINGER PROTEIN 1 (LZF1) and the negative regulators of photomorphogenesis phytochrome interacting factors PIF1, PIF3, B-BOX 25 (BBX25), B-BOX 28 (BBX28) directly interact with COP1, and their levels are regulated by the E3 ubiquitin ligase activity of COP1 (Holm et al 2002;Kim et al 2002;Datta et al 2006;Datta et al 2008aDatta et al , 2008bGangappa and Botto 2016;Xu et al 2016;Zhang et al 2017;Lin et al 2018;Heng et al 2019).…”
Section: Light Signalingmentioning
confidence: 99%
“…Upon light illumination, COP1 is inactivated via multiple regulatory mechanisms, releasing the positive photomorphogenesis regulators to function [22,23]. Recent findings have reported that B-box domain proteins (BBXs) function as positive and negative regulators of photomorphogenesis in the HY5-mediated pathway [24,25]. BBX28, BBX30, and BBX31 Inactive phytochrome (red light-absorbing Pr form) can be converted to active phytochrome (far-red light-absorbing Pfr form) by absorbing red light.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous genetic studies have shown that plants overexpressing BBX10, BBX19, BBX30, or BBX31 flower later than do wild-type plants, whereas bbx19 mutant and bbx30 bbx31 double mutant plants flower relatively early under long days (Wang et al 2014;Graeff et al 2016;Ordoñez-Herrera et al 2018;Heng et al 2019b), suggesting that all four BBXs act as repressors of flowering. Briefly, each of these proteins can physically associate with CO to inhibit its transcriptional activation activity toward FT, thereby delaying the photoperiod-induced floral transition (Wang et al 2014;Graeff et al 2016;Ordoñez-Herrera et al 2018) (Figure 1).…”
Section: Involvement Of Bbx In Floral Regulationmentioning
confidence: 99%
“…B-box protein24, BBX25, and BBX28 physically associate with HY5 to repress its transcriptional activation activity toward target genes, which in turn inhibits photomorphogenic development (Gangappa et al 2013;Lin et al 2018). Both BBX30 and BBX31 negatively control photomorphogenic development and act directly downstream of HY5, which directly associates with the G-box cis-element within the BBX30 and BBX31 promoter regions to inhibit their expression (Heng et al 2019b;Yadav et al 2019). B-box protein32 associates with BBX21 and suppresses the activity of BBX21, as well as its interacting partner HY5, eventually resulting in a negative regulatory effect on photomorphogenesis (Holtan et al 2011).…”
Section: Continuedmentioning
confidence: 99%
See 1 more Smart Citation